Musical theatre education and training in the 21st century - O'Bryan, Jessica; Harrison, Scott D. (Scott David), 1962- (Routledge, 2024)
"Musical Theatre Education and Training in the 21st Century presents a wide range of viewpoints on the musical theatre profession. It brings together research from the UK, US, Australia and beyond, providing an essential resource for educators, students, and all those involved in training for musical theatre. The research draws on best practice from creatives, producers, practising artists and the academy to reveal a multiplicity of approaches and educational pathways for consideration by performers, educators, institutions and the profession. The book goes beyond the key elements of performance training in singing, dancing and acting to explore adjacent creative and business skills, along with some of the more recent and challenging aspects of the profession such as diversity of representation both on and off stage, building safe working environments, and managing mental and physical health and wellbeing. The authors incorporate information from over 100 interviews with everyone from emerging performers to leading professionals, and explore the practicalities of pre-professional training, skills development and curricular design, alongside the broader attributes required in preparation for the profession. This book offers vital insights into how musical theatre practitioners can best be prepared to make their way in the field now and in the future"--